Examining progress in research on public value - Yotawut, Mayuree (My University, 2017)
This article reviews a new three-volume collection of previously published articles on how public or private organizations are operationalizing the principles of public value: firstly, ‘Measuring the public value of e-government: A case study from Sri Lanka’; secondly, ‘New Public Management to public value: Paradigmatic change and managerial implications’, and lastly, ‘Developing an understanding of result-based management through public value theory’. All three articles in this paper also explain how public value creates service, trust, and other positive outcomes, and how public organizations use public value in measuring the dimensions of public value generation in terms of e-government. Finally, an article on the idea of public value has been proposed as a way of understanding government activity, informing policy-making and constructing service delivery. Employing public value as a tool for result-based management through New Public Management, and achieving it through public organization is an essential recommendation of this article. © 2017 Kasetsart University. Publishing services by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/ 4.0/).
full text
Keywords: examining progress, public organization, public value